2015
DOI: 10.1177/0956462415624059
|View full text |Cite
|
Sign up to set email alerts
|

UK national guidelines on the management of syphilis 2015

Abstract: These guidelines are an update for 2015 of the 2008 UK guidelines for the management of syphilis. The writing group have piloted the new BASHH guideline methodology, notably using the GRADE system for assessing evidence and making recommendations. We have made significant changes to the recommendations for screening infants born to mothers with positive syphilis serology and to facilitate accurate and timely communication between the teams caring for mother and baby we have developed a birth plan. Procaine pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
215
0
36

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(258 citation statements)
references
References 116 publications
(234 reference statements)
7
215
0
36
Order By: Relevance
“…Tertiary syphilis involves a severe and self-destructive immune response to a persistent low level burden of T. pallidum 5. This can present as cardiovascular syphilis, gummatous syphilis, late benign syphilis or neurosyphilis 6. It is important to emphasise that neurological symptoms can occur during any phase of infection, and therefore neurosyphilis should only be considered tertiary when presenting in the late-latent period 5.…”
Section: Syphilis Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tertiary syphilis involves a severe and self-destructive immune response to a persistent low level burden of T. pallidum 5. This can present as cardiovascular syphilis, gummatous syphilis, late benign syphilis or neurosyphilis 6. It is important to emphasise that neurological symptoms can occur during any phase of infection, and therefore neurosyphilis should only be considered tertiary when presenting in the late-latent period 5.…”
Section: Syphilis Infectionmentioning
confidence: 99%
“…Guidelines currently recommend that, in the absence of central nervous system involvement, early (primary, secondary and early latent) syphilis should be treated with a single dose of benzathine penicillin G 2.4 million units (MU) intramuscularly, and late latent syphilis should be treated with three doses benzathine penicillin G 2.4 MU intramuscularly at 1-week intervals, regardless of HIV status (table 2). 6 Although this is the first-line recommended regimen, a large review found that in HIV-positive patients, it is associated with serological failure (defined as a less than fourfold decline in RPR/VDRL titre) in 0%–33% of cases. ART reduces this risk by roughly 60% 17…”
Section: Treatmentmentioning
confidence: 99%
“…5 When primary syphilis does occur in individuals with HIV, it is more likely to cause multiple ulcers rather than the classical single lesion. 6 HIV-positive individuals may also be more likely to develop neurological complications in the early stages of syphilis infection.…”
Section: Case Reportmentioning
confidence: 99%
“…The European Centre for Disease Prevention and Control (ECDC) [28] and the British Association for Sexual Health and HIV (BASHH) [29] suggest a different approach, meaning that a TT should be used first, followed by a second TT when reactive. Since POCT includes mostly TTs, this recommendation could be adopted everywhere and become universal.…”
Section: Syphilis Serological Diagnosis Algorithmsmentioning
confidence: 99%